Highly efficient visible-light-induced photocatalytic activity of Bi2WO6/BiVO4heterojunction photocatalysts - Saranyoo Chaiwichian (2018)
The Bi2WO6/BiVO4heterojunction photocatalysts were synthesized by hydrothermal method. Physical properties of the heterojunction photocatalyst samples were studied by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM) techniques. The XRD results indicated that BiVO4retain monoclinic and tetragonal structures, while Bi2WO6presented as orthorhombic structure. The Brunauer, Emmett and Teller (BET) adsorption-desorption of nitrogen gas for specific surface area determination at the temperature of liquid nitrogen was performed on all samples. UV-vis diffuse reflectance spectra (UV-vis DRS) were used to identify the absorption range and band gap energy of the heterojunction photocatalysts. The photocatalytic performance of Bi2WO6/BiVO4heterojunction photocatalysts was studied via the photodegradation of methylene blue (MB) under visible light irradiation. The results indicated that the heterojunction photocatalyst at 0.5:0.5 mole ratio of Bi2WO6:BiVO4shows the highest photocatalytic activity. © 2014 Elsevier Ltd. All rights reserved.